KEBERADAAN KESENIAN RABAB BADOI SEBUAH PENDEKATAN PENGGUNAAN DAN FUNGSI BAGI MASYARAKAT JORONG PAMATANG ANJUNG DI NAGARI MUARO KABUPATEN SIJUNJUNG - Alfahrus, Muhammad; Wimbrayardi, Wimbrayardi (SENDRATASIK UNP, 2019)
AbstractÂ The purpose of Rabab Badoi art study is to describe the existence of Rabab Badoi in the jorong Pamatang Anjung community, Nagari Muaro, Sijunjung Regency. This type of study was qualitative with using descriptive method that was to provide clearly about the object under study. The main instrument in this study was the researcher and it was assisted by using camera, stationery and interview lists. Techniques of data management were done by analyzing, classifying primary and secondary data and then compiling them systematically. The result of this study is the existence of Rabab Badoi Art in the terms of theirs use and function in jorong Pamatang Anjung, Nagari Muaro, Sijunjung Regency. Based on the aspect of the use, Rabab Badoi Art is played on the elevation of Pangulu, Bakau and Request of the Local Government. The functions of Rabab Badoi art were as emotional expression, communication, entertainment, community continuity.Keywords: existence, use, function, Rabab Badoi art